EVIDENCE OF THE CRIMINAL ACTOR OF THE VOTOR ANARCHIC MASS - Irma Nurmala Latief (2020)
This study aims to identify and explain about the regulation of prosecution against the criminal acts of anarchic mass rioters based on the provisions of the applicable laws. And to find out and explain about the legal process to prove the criminal responsibility of the perpetrators of mass rioting which are anarchist in nature. The theory used is the theory of proof and the theory of crime prevention. The research method used is a qualitative juridical analysis research method and the conclusion is drawn by the inductive method, which describes things that are specific to things that are general in nature in accordance with the problems discussed in this study. The results of this study are formulated that the Standard Operational Procedure of the State Police of the Republic of Indonesia regarding Anarchy Prevention can be explained by the efforts to anticipate anarchist actions that have an impact on mass riots carried out through several pre-emptive efforts, which are the initial actions taken by the Police in providing appeals and approaching demonstration groups. a feeling to demonstrate in an orderly manner; preventive efforts are efforts made by the Police in carrying out their duties in accordance with the Fixed Procedure (Protap); repressive measures are the police's last resort when the demonstrations and / or demonstrations are out of control and lead to riots. Conclusion; whereas the regulation of prosecution against perpetrators of mass rioting of an anarchic nature is based on the provisions of the criminal law in the offense of participation for the criminal responsibility of perpetrators of mass concessions that are anarchic in imposing crimes against the perpetrators, it is still necessary that the accuracy of the Judges' considerations in applying the inclusion offenses The application of the offense of participation in the legal process to prove the criminal responsibility of the perpetrators of mass rioting which is anarchic in nature can affect the effectiveness of the criminal sanctions imposed by the Judge in considering all evidence that is valid in the examination at trial requires the judge's accuracy, especially the expert's statement in making criminal decisions against the perpetrator. anarchist mass enterprise.